In vitro and in vivo Studies of Soybean Peptides on Milk Production, Rumen Fermentation, Ruminal Bacterial Community, and Blood Parameters in Lactating Dairy Cows - Xie, Tian; Kong, Fanlin; Wang, Wei; Wang, Yajing; Yang, Hongjian; Cao, Zhijun; Li, Shengli (Frontiers in Veterinary Science, 2022)
Soybean peptides (SPs), a feed additive derived from soybean, exhibit nutritional function and biological activity in monogastric animals, but limited studies have been conducted in dairy cows. Our experiments were conducted to evaluate the effects of SPs on the nutrient degradability of dry matter (DM), crude protein (CP), neutral detergent fiber (NDF) and acid detergent fiber (ADF) in vitro and milk production, rumen fermentation and bacterial community, and blood parameters of dairy cows. For in vitro experiment, ruminal fluids were collected from three ruminal cannulated Holstein dairy cows. Three levels of SPs (0, 0.38, and 1.92 g/kg DM of SPs) were added to the total mixed ration (TMR). Nutrient degradability and fermentation fluid pH were determined at 24 h and 48 h using 3.0 g samples of the substrate. Gas production after 48 h was recorded by an automated trace gas recording system using 0.5 g samples of the substrate. Results showed that DM , NDF, ADF(P < 0.01) and CP (P < 0.05) degradability were significantly increased at 1.92 g/kg DM of SPs at 24 h, and asymptotic gas production (P = 0.05) was increased at 48 h. For in vivo experiment, 110 lactating Holstein cows (209.7 ± 65.2 DIM; 37.2 ± 6.4 kg/d milk yield) were randomly assigned to 0 (control group, CON) or 50 g/head/day SPs (SPs-supplemented group). Yields of milk (P < 0.05), milk protein (P < 0.05), and milk lactose (0.05 < P < 0.10) increased on SPs supplementation; however, the milk fat percentage decreased (P < 0.05). The concentrations of individual volatile fatty acids (VFAs) (P < 0.05) and superoxide dismutase (SOD) (P < 0.01) were also increased. Rumen bacterial diversity in SPs-supplemented cows was higher (P < 0.05). The relative abundances of Rikenellaceae_RC9_gut_group, Butyrivibrio, Selenomonas, and Shuttleworthia were significantly increased and that of Coprococcus was decreased (P < 0.05). Our results showed that supplementing 1.92 g/kg DM of SPs could improve the nutrient degradability was increased in vitro and 50 g/head/day of SPs could improve milk production and antioxidant ability of dairy cows. The rumen bacterial diversity was also enhanced by SPs supplementation.